(untitled) (Fiep Bulletin - online, 2015)
The heading of this lecture, kindly suggested by the organizing Committee of the International Congress for the Integral Study of Sport, implies a Great power esposé. Hence its difficulty. However, taking into consideration that it is a theme of much interest and actuality, that I preside over such a widespread international organization which is 45 years old; that I myself am much older and have travelled over 4 Continents studying the problem which reunites us here, I could not refuse the testimony of a large personal experience.